Study on the mechanical properties of PES-HmA samples printed by selective laser sintering under various pre-heating conditions - Guo, Chengbo; Guo, Yanling; Li, Jian; Wang, Yangwei; Dai, Jiaming (Frontiers in Materials, 2024)
The purpose of this study is to investigate the influence of pre-heating characteristics on the mechanical properties and forming process of selective laser sintering (SLS) printed PES-HmA samples. An experimental setup with four heating tubes was designed to study the pre-heating temperature distribution on the powder bed. The pre-heating temperature distribution on the powder bed was captured using a thermal imaging camera. A method for evaluating pre-heating temperature distribution based on the average and standard deviation of surface temperature was proposed. The heating tube installation position was optimized using a response surface experiment study based on the temperature distribution evaluation. By optimizing the installation position of the tubes, the temperature distribution on the powder bed tends to become uniform. The effect of pre-heating temperature value and distribution on the mechanical properties of the SLS printed PES-HmA samples was also experimentally investigated. The cross sectional microstructure of the printed samples were examined by scanning electron microscope to analyze the layer formation process at different pre-heating temperature. By increasing the pre-heating temperature from 70°C to 100°C, the material diffusion at the layers interface was improved, which made the tensile strength of sample increased by 376%, and the flexural strength increased by 224%.